Back Pain in a Bangladeshi Worker in Iraq. Issue 1 (1st March 2010) - White, SH; Dickson, S; Colman, T; Hoque, F; Boos, Christopher
Abstract : Pyogenic Spinal Infection (PSI) is an uncommon disorder encompassing a broad spectrum of diseases including septic spondylodiscitis, osteomyelitis, epidural and paravertebral abscess formation. Presentation can be vague and highly variable but usually includes back pain and fever. Whilst predisposing factors, such as trauma and diabetes can often be identified a pathogenic organism may not be identified in up to a half of all cases leading to significant delay in both accurate diagnosis and effective treatment. Precise spinal imaging is essential and includes plain X-ray, CT and preferably MRI. The treatment of PSI can be conservative (including antibiotics); however, spinal surgery may be required for the complications in up to 50% of cases, with varying degrees of success. We present a challenging case of PSI encountered in a locally-employed 42 year-old Bangladeshi civilian working in Iraq. Despite obvious resource limitations available within a Role 2 Field Hospital, clinical suspicion coupled with repeat spinal CT was pivotal in obtaining the diagnosis. The patient was repatriated to Bangladesh for MRI and definitive surgical treatment.